Analisis Pusat Pelayanan Kegiatan Minapolitan - Dewi Purnama Sari (LPPM ITK, 2020)
Tabalong Regency based on Regional spatial Plan (RTRW) of South Kalimantan Regency 2014-2034 has the potential to be developed into a Minapolitan region. In principle, Minapolitan is a fishery program that seeks to synergize the production of raw materials, processing and marketing in a series of major activities in one area or region with the concept of involving the entire community in It. With the increase in the population of Tabalong Regency, it makes the need to increase the facilities available in the area as a factor in driving service and activities of fisheries by looking at the area that is the center of growth For the area that has a level of facilities that have a lack of the hierarchy in each district by conducting a system analysis of service center with the results of which 12 sub-districts that have the Minapolitan activities of Tanjung District become The centre of Minapolitan activities with Murung Pudak Sub-district became its sub-center of activities. With other sub-districts as a supporting area of Minapolitan activities. Keyword: Marketing, Minapolitan, Production